2023
DOI: 10.3390/atmos14111640
|View full text |Cite
|
Sign up to set email alerts
|

Chemical Composition and Source of PM2.5 during Winter Heating Period in Guanzhong Basin

Lei Cao,
Yanan Tao,
Hao Zheng
et al.

Abstract: An intensive field campaign was carried out from December 2022 to March 2023 at six different sites across five major cities (Xi’an, Baoji, Xianyang, Weinan, and Hancheng) in the Guanzhong Basin, China, covering most of the heating period there, which is characterized by high PM2.5 pollution levels. During the campaign, the mean PM2.5 concentrations at these sites exceeded the 24 h PM2.5 standard (75 μg m−3), except the site at Hancheng, with mean PM2.5 concentrations of 57.8 ± 32.3 μg m−3. The source apportio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 43 publications
0
1
0
Order By: Relevance
“…However, the common sources of pollution in the four years were transportation sources and coal burning. Liu et al analyzed the composition of fine particles in winter in Taiyuan and found that inorganic sulfate and organic PAHs were important components of PM 2.5 [34].…”
Section: Pahs Health Risk Assessmentmentioning
confidence: 99%
“…However, the common sources of pollution in the four years were transportation sources and coal burning. Liu et al analyzed the composition of fine particles in winter in Taiyuan and found that inorganic sulfate and organic PAHs were important components of PM 2.5 [34].…”
Section: Pahs Health Risk Assessmentmentioning
confidence: 99%